Experimental study of the effect of 2/1 classical tearing mode on (intermediate, small)-scale microturbulence in the core of an EAST L mode plasma. (5th January 2018) - Sun, P J; Li, Y D; Ren, Y; Zhang, X D; Wu, G J; Lyu, B; Shi, T H; Xu, L Q; Wang, F D; Li, Q; Zhang, J Z; Hu, L Q; et al.
Abstract: In this paper, we report an experimental study of the effect of a m / n  = −2/−1 ( m, n being poloidal and toroidal mode number, separately) classical tearing mode on (intermediate, small)-scale microturbulence (see the definition in section1 ) in the core of an EAST L mode plasma discharge. The microturbulence at different scales k ⊥  = 10, 18 and 26 cm −1 (i.e., k ⊥ ρ i ∼ 2, 3.6 and 5.2, respectively. Here, ρ i is the ion gyroradius and k ⊥ is the perpendicular wavenumber) were measured simultaneously by the EAST multi-channel tangential CO2 laser collective scattering diagnostics. Experimental results confirm that the decrease of microturbulent Doppler shift ( f Doppler = k t v t / 2 π ), inversely correlated to the increase of microturbulent mean frequency (defined in equation (1 )), is due to the 2/1 tearing mode. Temporal evolution of frequency-integrated spectral power S tot of microturbulence, found to be correlated with the width of 2/1 magnetic island, suggests the modulation effect on microturbulence by the tearing mode beyond Doppler shift effect. Modulation effects on microturbulence by the tearing mode are further demonstrated by the correlation between microturbulent envelope and magnetic fluctuations.